1990
DOI: 10.3109/15563659008994432
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Pathology in Adult Iron Overdose

Abstract: The gastrointestinal effects of iron overdose have been described in children. They may occur acutely, ranging in severity from mucosal injury to complete infarction, or several weeks later, as obstruction due to stricture formation. They typically occur in the stomach or proximal small bowel. We describe an adult example of both, each occurring in the distal portion of the small intestine. Both patients had ingested enteric-coated iron preparations and both experienced significant, protracted abdominal pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…40 This poisoning can cause bloody diarrhea and vomiting due to the damage of the intestinal epithelial linings. 41,42 Erosive injury to the upper gastrointestinal tract in patients receiving iron medication has been reported as a side effect. 43 In the present experiments, ferric citrate was easily absorbed, leading to extremely high levels of iron in the liver both in TGs and wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…40 This poisoning can cause bloody diarrhea and vomiting due to the damage of the intestinal epithelial linings. 41,42 Erosive injury to the upper gastrointestinal tract in patients receiving iron medication has been reported as a side effect. 43 In the present experiments, ferric citrate was easily absorbed, leading to extremely high levels of iron in the liver both in TGs and wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the histolesive action of some agents on the gastrointestinal tract is aggra vated by the simultaneous induction of con tractions [14]. Thus, the ferrous sulfate-in-duced alterations in motor activity demon strated in the present study may contribute to the histological damage observed in iron overdose [15].…”
Section: Gastrointestinal Damagementioning
confidence: 53%
“…Erosive injury to the mucosa of the upper GI tract is well known in the context of overdoses of oral iron supplements 1 2. However, such injury in the context of therapeutic dosing is less well recognised.…”
Section: Discussionmentioning
confidence: 99%
“…While erosive injury to the mucosa of the upper gastrointestinal (GI) tract is a well-recognised consequence of overdose with oral iron supplements,1 2 similar injuries can result from doses in the normal therapeutic range. In this case, the associated endoscopic and radiological features were highly suggestive of malignancy—a presentation that has not previously been reported.…”
Section: Introductionmentioning
confidence: 99%